Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Di Desa Plampang Kecamatan Paiton - Fatmala, Kiki; Hukmah, Safiroh (Jurnal Samudra Ekonomika, 2024)
This study aims to determine the effect of land area, labor and total cost on the income of farmers in Plampang village, Paiton sub-district. The research data used is primary data. The regression equation obtained is Y=-961600.747 + 29987.839 (La) + 139869.432 (Tk) + 350 (M).The results of t-test show that each variable of land area, labor and capital has a positive and significant effect on farmers' income in Plampang Village. The results of F test show that land area, labor and capital have a positive and significant effect on farmers' income in Plampang Village, Paiton Subdistrict. The coefficient of determination R Square is 0.913, which means that the variables of land area, labor and capital affect the income of farmers 91.3%.